Pengaruh Layanan Informasi tentang Pendidikan Seks terhadap Peningkatan Sikap Seks Sehat Siswa Kelas XI IPS SMA Negeri 2 Siakhulu T.P 2014/2015 - Munawir '; Raja Arlizon Arlizon; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Information about sex is important given to students so that students can move away from free sex and maintain reproductive health. This study aims to determine the service process, influence of information services on sex education and healthy sex differences in students attitudes before the services performed after information. This research method is experimental method. Subjects of this study and the sample totaled 143 sudents were taken by purposive sampling technique were 107 foreign students from students SMAN 2 Siakhulu. Results of this study are in the process of providing student services initially shy and stiff implement, after going trouhgh a gradual five meetings, students no longer shy and stiff discuss it and come to know the positive impact of sex education. r test results show r , r count > r table (0,55 > 0,195), then there is a significant positive effect on sex education information services to students healthy sex students. While t count > t table (8,12 > 1,960), so there are significant differences betwen the attitudes of students healthy sex before with after the implementation of information about sex education. Key Words : sex education, students healthy sex